Platform-Enabled Horizontal Collaboration Strategy as a Strategy to Improve the Sustainable Logistics Performance of Logistics Companies - Dani Leonidas Sumarna; Vanessa Gaffar; Lili Adi Wibowo; H. Mokh. Adib Sultan (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The logistics sector in Indonesia faces high costs, infrastructure gaps, and turbulence from e-commerce growth and regulatory changes, especially in West Java, a key hub for third-party logistics providers. Digital transformation promises better efficiency, but many firms fail to convert digital tools into balanced sustainable performance across economic, environmental, and social dimensions. This study examines how logistics ecosystem turbulence and digital logistics agility affect sustainable logistics performance among third-party logistics firms in West Java. It also investigates the mediating roles of platform-enabled horizontal collaboration strategy, customer experience management, and competitive implementation through single and sequential paths. Data were collected via a cross-sectional survey from 312 valid respondents and analyzed using partial least squares structural equation modeling. Findings indicate that logistics ecosystem turbulence, platform-enabled horizontal collaboration strategy, customer experience management, and competitive implementation significantly and positively influence sustainable logistics performance. Digital logistics agility shows no direct effect. Mediation analysis reveals platform-enabled collaboration as a central link between turbulence/digital agility and sustainable outcomes, while customer experience management and competitive implementation are key mechanisms that turn collaboration into performance gains. Sequential mediation confirms sustainable results arise from interconnected steps: collaboration followed by customer focus and strong execution.